Prognostic value of HSP27 in 28-day mortality in septic ICU patients: a retrospective cohort study - Lihua Yao; Lihua Yao; Zaiwei Fan; Fangyi Yao; Xiaozhong Wang (Frontiers in Medicine)
BackgroundThis study aimed to investigate the association between serum heat shock protein 27 (HSP27) levels and 28-day mortality in patients with sepsis.MethodsThis retrospective study analyzed the clinical data of 76 septic patients admitted to the intensive care unit (ICU). Fifty non-septic ICU patients and 50 healthy individuals served as control groups. Serum HSP27 levels were measured on the day of ICU admission and compared to sepsis severity and survival outcomes.ResultsMedian serum HSP27 levels in septic patients (4.70 ng/mL, IQR: 2.10–13.48 ng/mL) were significantly higher than those in both non-septic ICU controls and healthy controls (all p < 0.05). Moreover, non-survivors exhibited significantly higher median HSP27 levels (9.30 ng/mL, IQR: 3.62–25.91 ng/mL) compared to survivors (3.03 ng/mL, IQR: 1.48–7.39 ng/mL, p < 0.05). Multivariate logistic regression analysis confirmed the association between HSP27 levels and 28-day mortality in sepsis patients. Receiver operating characteristic (ROC) curve analysis revealed an area under the curve (AUC) of 0.720 (95% CI: 0.605–0.817, p < 0.001) for HSP27 in predicting sepsis prognosis. Survival analysis demonstrated that patients with high serum HSP27 levels (≥2.61 ng/mL) had a worse prognosis than those with low levels (<2.61 ng/mL).ConclusionHSP27 shows potential as a biomarker for the diagnosis and prognosis of sepsis, however, further research is necessary to solidify its clinical utility.